(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The violation of obligations by the auditors in the organization has become an issue of a major and hot concerned in Saudi Arabia particularly with the scandals of MMG (Mohammad Al Mojil Group) and Etihad Etisalat also known as Mobily. The gaps in auditors’ obligations and responsibilities served to bring about violations of obligations by the auditors. This study investigations how gaps in auditors’ obligations and responsibilities lead to violations of obligations in Saudi Arabai. Also, the study attempted to know which factor is the most significant variable that led to violation of obligations by the auditors. The study adopted a cross-sectional survey research design with a total of 300 respondents (comprising of auditors from various firms in Saudi Arabia) were surveyed regarding violation of obligations and responsibilities in Saudi firms using a quantitative approach. The quantitative data generated were analysed using both Ordinary Least Square (OLS) and Stepwise regression analysis techniques. From the finding, it is revealed that the gaps in auditors’ obligations and responsibilities lead to violations of obligations in Saudi Arabia, the gaps in auditors’ obligations and responsibilities significantly affect violations of obligations in Saudi Arabia (p<0.05, p=0.000). The finding further from the stepwise regression revealed that Friendly relationship with the client is the most important variable that leads to the violation of obligations by the auditors with a beta value .654, thus, highlight the significant positive impact of Friendly relationship with the client on violations of obligations by the auditors in Saudi firms. This is equally followed by anability to follow standards by the auditors with a beta value of .354, suggesting its importance in violation of obligations by the auditors. Other variables leading to violations of obligations as captured by the finding include unethical practices, auditor’s negligence and accounting and auditing failures with beta values of .262, -.182 and .135. Drawing from the findings, the study concluded that gaps in auditors’ obligations and responsibilities lead to violations of obligations by the auditors. Additionally, the study also concluded that friendly relationship with the client is the most important variable that leads to the violation of obligations by the auditors, and this revealed the significant positive impact of friendly relationship with the client on violations of obligations by the auditors in Saudi firms.This research fills a void in research in this area in a country like Saudi Arabia small country. These findings have important implications for all stakeholders, particularly investors, auditors and regulators.